Business income and passive income in the UN model double taxation convention - Mascia, Susanna (LUISS Guido Carli, 2013)
The historical evolution of the UN model convention. The UN model convention’s subjective and objective scope. The determination of active income: current points of difference between the UN and OECD models. The determination of passive income: differences and similarities between the UN and the OECD model conventions. Transfer pricing.